Optimization and validation of a method for extraction and quantification of ochratoxin A in black pepper - Jalili, Maryam; Selamat, Jinap (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
The extraction method for the determination of ochratoxin A (OTA) in black pepper was optimized. The influence of three variables, i.e., type of solvent, solvent-volume-to-sample-size ratio (v/w) and amount of sodium chloride (NaCl) (g), on OTA recovery was evaluated. Analysis of variance was used to compare recovery values obtained from different solvents, and response surface methodology (RSM) was used to determine the optimum amount of NaCl and the solvent-volume-to-sample-size ratio. The concentration of OTA was determined by high-performance liquid chromatography with fluorescence detection. The highest recovery (95.2 %) was obtained when methanol/water (80:20, v/v) was used as the solvent. The RSM results showed that the experimental data could be adequately fitted to a second-order polynomial model with multiple regression coefficients (R2) of 0.962. The optimum amount of NaCl was determined to be 3 g, whereas the optimum solvent-volume-to-sample-size ratio (v/w) was found to be 4. The proposed method was applied to 20 samples, and the presence of OTA was found in 8 (40%) samples ranging from 0.11 to 3.16 ng g-1.